Letter: a 5‐year long‐term follow‐up study after DAA treatment confirms a reduced HCC risk in a central European cohort of HCV patients with liver cirrhosis. Issue 1 (18th December 2019) - Ebel, Friederike; Deterding, Katja; Port, Kerstin; Schlevogt, Bernhard; Manns, Michael P.; Maasoumy, Benjamin; Cornberg, Markus; Wedemeyer, Heiner
Abstract : LINKED CONTENT This article is linked to Mecci et al paper. To view this article, visit https://doi.org/10.1111/apt.15296 .